2016
DOI: 10.1097/sla.0000000000001139
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gastric Bypass on Gastroesophageal Reflux Disease in Morbidly Obese Patients

Abstract: For most morbidly obese patients, in addition to causing significant weight loss, GBP reduces GERD symptoms, improves reflux esophagitis, and decreases esophageal acid exposure for longer than 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 53 publications
1
54
0
7
Order By: Relevance
“…Clinical examination and specific questionnaires (such as the GORD questionnaire) may lead to false‐positive or false‐negative diagnoses of GORD. Furthermore, previous studies reported difficulty in diagnosing GORD in morbidly obese patients, according to the Montreal Consensus, with limited sensitivity and negative predictive value in such patients. Twenty‐four‐hour pH monitoring remains an objective method for assessing GORD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical examination and specific questionnaires (such as the GORD questionnaire) may lead to false‐positive or false‐negative diagnoses of GORD. Furthermore, previous studies reported difficulty in diagnosing GORD in morbidly obese patients, according to the Montreal Consensus, with limited sensitivity and negative predictive value in such patients. Twenty‐four‐hour pH monitoring remains an objective method for assessing GORD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even with the Montreal Consensus definition of GORD, diagnosis may be difficult in severely obese patients because of the limited sensitivity and negative predictive values of criteria in these patients. Twenty‐four‐hour pH monitoring could be an objective means of assessing GORD in such patients.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, following RYGB, all pH-based parameters, such as esophageal acid exposure, percent time at esophageal pH<4, number of reflux episodes, number of reflux episodes lasting greater than 5 min, and DeMeester score, have been shown to improve significantly in short-and long-term studies. 13,16 Additionally, esophagitis was resolved after RYGB in most case series. Finally, Frezza et al demonstrated that, in addition to typical symptoms, atypical symptoms of GERD, such as wheezing, laryngitis, and aspiration, which are often refractory to conventional medical therapy, were also improved after RYGB.…”
Section: Gastric Bypassmentioning
confidence: 84%
“…This finding has been attributed to a wide array of factors, including increased abdominal pressure, decreased lower esophageal sphincter pressures, esophageal motility disorders, and an increase in anatomical abnormalities, such as hiatal hernia [11]. Roux-en-Y gastric bypass has been demonstrated to lead to high rates of resolution of GERD in affected patients [5,12,13]. The mechanisms of GERD control are multifactorial and include mechanical diversion of acid and digestive enzymes from the esophagus and reduced pressure gradient between the abdominal and thoracic cavity through weight loss [14].…”
Section: Discussionmentioning
confidence: 95%
“…A study published using the national Bariatric Outcomes Longitudinal Database (BOLD) revealed that 32 % of more than 100,000 patients to undergo bariatric surgery in a 30-month period across the country had evidence of GERD preoperatively [4]. The laparoscopic Roux-en-Y gastric bypass has been demonstrated to result in a high rate of resolution of GERD in affected patients [5]. In contrast, the sleeve gastrectomy has a lower rate of GERD resolution and a higher rate of de novo GERD in published studies, although some controversy remains [6,7].…”
mentioning
confidence: 98%